Relatório do estágio curricular supervisionado em Medicina Veterinária – área: clínica cirúrgica de pequenos animais - (:unkn) unknown (Universidade Federal do Pampa, 2019)
The purpose of this report is to describe the activities carried out by the academic researcher Natália Reginato Lazzari on Supervised Curricular Internship in Veterinary Medicine (ECSMV) held at the Federal University of Santa Maria (UFSM) at the Hospital Veterinário Universitário (HVU) in the surgical clinic area of little animals. The internship was carried out under the guidance of Professor Dr. Diego Vilibaldo Beckmann and the activities were supervised by the veterinarian Dr. Maicon Pinheiro from January 28 to April 19, 2019, totaling 523 hours. During the ECSMV, the academic had the opportunity to monitor and assist routine clinical and surgical care and surgical procedures HVU hospital. In the present study, three surgical cases are reported occurred in canine species, namely: 1) juvenile pubic symphysiodesis; 2) Abscess canine paraprostatic; 3) Osteosynthesis of right ilium with cerclage wire. At developed activities brought extensive knowledge through different technical conducts adopted, as well as different clinical and surgical cases that could be directly or indirectly accompanied by the academic during this period.
Report of the supervised curricular internship in veterinary medicine - area: small animal surgical clinic
Keywords: Medicina veterinária; Clínica médica veterinária; Clínica de pequenos animais; Cirurgia veterinária; Técnica cirúrgica; Sinfisiodese púbica juvenil; Abscesso paraprostático; Osteossíntese de ílio; Veterinary medicine; Veterinary medical clinic; Small animal clinic; Veterinary surgery; Surgical technique; Juvenile pubic symphysiodesis; Paraprostatic abscess; Osteosynthesis of ilium; CNPQ::CIENCIAS AGRARIAS